2018
DOI: 10.1509/jm.16.0267
|View full text |Cite
|
Sign up to set email alerts
|

Relational Price Discounts: Consumers’ Metacognitions and Nonlinear Effects of Initial Discounts on Customer Retention

Abstract: Practitioners increasingly employ relational price discounts by granting initial discounts to new customers with the goal of building sustainable relationships. However, extant research has provided mixed findings on the long-term effects of initial discounts on customer retention. The current research aims to reconcile this mixed evidence by exploring nonlinear effects of initial discounts on customer retention. Drawing on marketplace metacognition theory, the authors hypothesize that moderate initial discoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 68 publications
(118 reference statements)
0
24
0
Order By: Relevance
“…To further examine the effect of sustainability on perceived product performance, we used spotlight analysis (Aiken and West 1991) at one standard deviation below and above the mean of environmental values ( M = 3.92 vs. M = 6.42) while controlling for product category (see Figure 1). We used cluster‐robust standard errors to account for the panel structure of the data (Mizik & Jacobson, 2009; del Rio Olivares et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…To further examine the effect of sustainability on perceived product performance, we used spotlight analysis (Aiken and West 1991) at one standard deviation below and above the mean of environmental values ( M = 3.92 vs. M = 6.42) while controlling for product category (see Figure 1). We used cluster‐robust standard errors to account for the panel structure of the data (Mizik & Jacobson, 2009; del Rio Olivares et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…When perceived value increases, higher levels of relationship equity should more readily translate into brand equity as a result of the reciprocal responses;, because the consumers interpret the increased value as a relationship-building effort of the brand (Fazal-e-Hasan et al , 2018). For instance, granting initially moderate discounts to new customers might, in return, activate the customers’ motive to build long-term relationships with brands (del Rio Olivares et al , 2018), which subsequently enhances consumers’ brand equity and accelerates their purchases (Dwivedi et al , 2012; Inman et al , 1997). In the context of service branding, consumers perceiving that switching costs outweigh switching benefits are more inclined to maintain the relationship with a brand regardless of their satisfaction level with that brand (Lee and Cunningham, 2001; Jones et al , 2000).…”
Section: Literature Review and Theoretical Modelmentioning
confidence: 99%
“…Yet Kalwani and Yim (1992) cautioned that consumers form discount expectations after being exposed to frequent discounts and thus may start to purchase discounted products only. In their meta-analysis, DelVecchio, Henard, and Freling (2006) indicated that price discounts greater than 20% negatively influence sales in the long run, although other studies have claimed that a moderate discount depth (about 30%) is most effective (e.g., Andrews et al 2014;Del Rio Olivares et al 2018). Hence, prior studies also point to the importance of accounting for consumer discount expectations and for nonlinear effects of discounts on consumer purchase behavior.…”
Section: Literature Reviewmentioning
confidence: 99%